THE RELATIONSHIP BETWEEN TEACHER SALARY AND STUDENT DEVELOPMENT IN CLASS - I GUSTI NGURAH OCTAVA SEVENTILOFA (SOSIAL SAINS DAN TEKNOLOGI, 2023)
This research critically investigates the intricate relationship between teacher salary and student development within the classroom context, aiming to discern the multifaceted impacts of educators' compensation on the academic achievements and holistic growth of students. Employing a quantitative research design with a diverse sample of teachers and students across educational institutions, the study delves into the potential correlations between varying levels of teacher salaries and the progress of learners. Drawing on theoretical frameworks such as Human Capital Theory and Motivation Theory, the research seeks to elucidate the economic and motivational dimensions that potentially link teacher salaries to student outcomes. The data analysis involves sophisticated statistical techniques, including regression modeling and correlation studies, to comprehensively examine the strength and nature of the relationship between teacher salaries and student development. The significance of this research lies in its potential to inform educational policies and practices, offering insights into the crucial role of teacher compensation in fostering optimal student development and contributing to the ongoing discourse on effective educational strategies. The findings are expected to have implications for policymakers, educators, and stakeholders, guiding their efforts to enhance the educational landscape and ensure the creation of conducive learning environments that attract and retain high-quality educators